2019
DOI: 10.1002/adsc.201801471
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Iron‐Catalyzed Reactions towards the Synthesis of Nitrogen‐Containing Heterocycles

Abstract: Heterocycles are generally biologically active compoundsa nd find widespread applications in medicinalc hemistry,a gricultural science and the fine chemical industry.F or the synthesis and functionalization of heterocycles,g reat efforts have been ascribed over the past decades.T he syntheses of heterocyclic compounds are significant due to their diverse biological activity.R ecently,i ron-catalyzed reactions have experienced remarkable progress in the synthesiso fh eterocycles.T hisr eview summarizes recent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 96 publications
0
18
0
1
Order By: Relevance
“…[26] Numerous methods have been developed for the synthesis of tetrazoles, [20,27,28] they have been generally synthesized by [3 + 2]-cycloaddition reaction between nitriles and azides in the presence of various transition metal catalysts, such as Pd, [20,28,29] Ni, [22,30,31] and iron compounds. [32][33][34] Methods for the synthesis of 5-substituted 1H-tetrazoles from aldoximes or aldehydes in the presence of copper (II) catalysts have also been reported. [35] However, some methods have disadvantages such as the need for toxic metals and explosive azide sources.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Numerous methods have been developed for the synthesis of tetrazoles, [20,27,28] they have been generally synthesized by [3 + 2]-cycloaddition reaction between nitriles and azides in the presence of various transition metal catalysts, such as Pd, [20,28,29] Ni, [22,30,31] and iron compounds. [32][33][34] Methods for the synthesis of 5-substituted 1H-tetrazoles from aldoximes or aldehydes in the presence of copper (II) catalysts have also been reported. [35] However, some methods have disadvantages such as the need for toxic metals and explosive azide sources.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that despite changing R 1 in thioureas, the structure of all final compounds looks quite similar. Comparatively experimental results revealed that the selection of R 1 = CH3, C2H5, CN, NO2 either in para or meta positions led to the same product [R 1…”
Section: Methodsmentioning
confidence: 99%
“…Fused heterocyclic compounds are the key valuable and structural scaffolds in a broad variety of natural products, drug molecules, and functional materials [1][2][3]. Among them, the analogues of benzothiazole and its derivatives have a significant role due to their wide variety of biological activities and applications in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…They have wide range of applications and are powerful tools in small molecule synthesis . Even though, Palladium is the most widely used catalyst in transition metal catalysis Ag, Fe, Zn, Cu, Mn, Co, Ni etc… are also efficiently utilised now a days …”
Section: Introductionmentioning
confidence: 99%